Leonidam Rozem 100 - Vilka, Gunta (LU Muzejs, 2025)
Latvijas Universitātes astronomam, vēsturniekam un ilggadīgajam žurnāla “Zvaigžņotā Debess” redkolēģijas loceklim Leonidam Rozem 2025. gada 20. maijā atzīmējam 100 gadu jubileju. Šajā rakstā aplūkota viņa dzīve un darbība Latvijas Valsts universitātes Astronomiskajā observatorijā.

On May 20th 2025, we celebrate the 100th anniversary of Leonid Roze, an astronomer at the University of Latvia, historian, and long-time member of the editorial board of the journal "Starry Sky". This article introduces with his life and work at the Astronomical Observatory of the Latvian State University.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics::Astronomy and astrophysics::Astronomy; Leonids Roze; Astronomija; Astronoms; LU Muzejs; Latvijas Universitāte; Astronomiskā observatorija; Leonids Roze; Astronomy; Astronomer; The Museum of the University of Latvia; The University of Latvia; Astronomical Observatory